Routledge handbook of Africa-Asia relations
1 online resource (xxi, 483 pages)
Keywords: "The Routledge Handbook of Africa-Asia Relations is the first handbook aimed at studying the interactions between countries across Africa and Asia in a multi-disciplinary and comprehensive way. Providing a balanced discussion of historical and on-going processes which have both shaped and changed intercontinental relations over time, contributors take a thematic approach to examine the ways in which we can conceptualise these two very different, yet inextricably linked areas of the world.Using comparative examples throughout, the chronological sections cover: Early colonialist contacts between Africa and Asia; Modern Asia-Africa interactions through diplomacy, political networks and societal connections; Africa-Asia contemporary relations, including increasing economic, security and environmental cooperation.This handbook grapples with major intellectual questions, defines current research, and projects future agendas of investigation in the field. As such, it will be of great interest to students of African and Asian Politics, as well as researchers and policymakers interested in Asian and African Studies."--Provided by publisher.